GLOBALIZATION EFFECTS ON SOCIETY. CASE STUDY: THE DYNAMICS OF FOREIGN DIRECT INVESTMENT IN POST-COMMUNIST ROMANIA (PANGEEA, 2025)
Abstract. Globalization is a reality of the contemporary world, with manifestations and effects connected to all levels of human activities: economic, political, social, cultural, scientific and ecological. The suspension of customs barrier, the emerge of multinational companies, the competition on foreign and domestic markets, the importance of the resources and the way they are consumed have become causes and effects of the globalization. This study is meant to be an overall assessment of its effectts in a post-communist Romanian society. A more detalied analysis focuses on a trends and spatial features of foreign direct investment (FDI) seen mainly as a tool of the economic globalization. The foreign investment dynamics in Romania registered a positive trend after the communist fall. This is due to the massive flow of foreign investments from E.U. and also the economic performanced made by our country.
Keywords: globalization; foreign investment; economical rise; trade